OPTIMIZATION OF THE HYDRAULIC SYSTEM IN THE EXCAVATOR ARM SIMULATOR - Abdul Azis Abdillah (Jurnal Poli-Teknologi, 2021)
Most of the heavy equipment units use a hydraulic system, even including systems that are essential for working with a heavy equipment unit. The hydraulic system is a system that utilizes a liquid medium in the form of fluid or oil to generate pressure, which is used to implement, the power train system, the disconnection system, the steering system. The working principle of hydraulics is to utilize the pressure exerted on the tool (which is used for this actuator / cylinder / tube) so that the pressure pushes the piston which is connected to the rod. The hydraulic system in this study is an arm excavator. This simulator is like a hydraulic system in general which consists of a power unit, in this simulator the power unit used is a type of electric motor that is connected to a hydraulic pump. The control unit is in the form of a control valve. The drive unit is an actuator / cylinder / tube. This simulator has been disabled for a long time due to a malfunction. Then the authors performed a simple analysis and improvements to the excavator arm simulator. So the research that is done is to do the 8 step troubleshooting method on the simulator. This step aims to facilitate the repair process in the simulator.